Scaling factors for 1-D ground response amplification in a soft soil basin - Apriadi, Dedi; Mandhany, Anggariano; Sahadewa, Andhika; Basarah, Yuamar I.; Sengara, Wayan; Hakim, Abi Maulana (Frontiers in Built Environment, 2024)
Basin presence is believed to affect ground surface response due to earthquakes, particularly in areas around the basin edge. Previous studies showed that 1-D and 2-D wave propagation analyses resulted in significant difference in amplification at the basin edge. However, the link between 1-D and 2-D responses has not been studied for engineering practices. In practical application, seismic studies were commonly performed using 1-D analysis, for example to develop a city micro zonation map. Based on practical considerations, it is necessary to estimate the scaling factor for the 1-D analysis by considering the basin presence, particularly for one containing soft soil. There are three stages carried out in this study. The first stage: collecting data on some basin geometries for the 2-D modeling references and then defining selected site class and input motions. The second stage: modeling 1-D and 2-D wave propagation using DMOD and FLAC, respectively. The third stage: comparing spectral acceleration resulting from the 1-D and 2-D analysis to obtain the scaling factors. This research studied and reported the relationship between PGA was varied as 0.2g, 0.3g, 0.4g, and 0.5g, basin geometry (e.g., angle was set to 5°, 10°, 15°, 30°, to 45°, depth and width variations were 0.0125, 0.025, 0.05, 0.075, 0.1, 0.2, and 0.4 with the basin width was adjusted to 500 m, 1 km, 2 km, and 4 km), and the spectral acceleration in several observation points on the ground surface. Based on this evaluation, a series of scaling factors are proposed. These factors can be used for spectral acceleration from available hazard maps, commonly developed based on 1-D analysis. Application example of this scaling factor is presented in this study, using Bandung basin case.